ISLAMIC ECONOMIC CONSTRUCTION TOWARDS DEVELOPMENT CIVIL SOCIETE - Yaqin, Ainol (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of this community service paper is to find the basic framework for the construction of Islamic economics for the development of civil society, an offer for government authorities, the Association of Islamic Economic Experts (IAEI), the National Islamic Economic Committee (KNEKS), Islamic boarding schools and Muslims. The economic system adopted by most people in this part of the world has failed to create a prosperous society and build harmony. However, has created economic pressure. They have failed to reduce poverty. This community service paper model is a proposal, socialization and advice for government authorities, Islamic institutions and boarding schools to implement Islamic Economic Construction towards civil society. This paper concludes that the construction of Islamic economics towards the development of civil society includes: 1. Tauhid, all economic resources are God's creation, and their arrangement and distribution must be by the rules. 2. Nubuwwah, all sources and economic policies must be guided by the Prophet, who has successfully created social welfare. 3. Adl (justice), the principle of justice, is the basis for building civil society and creating equal access to meeting needs. 4. The Khilafah government is essential for the sustainability of the Islamic economy, which aims at the welfare of society. Without the role of the government, implementing Islamic economics is impossible to materialize. 5. Maad, profit from Islamic economics is the goal of economics, especially the results that can later be taken in the hereafter, and has two dimensions, namely profit (economic) and success in the hereafter.